Sleeping arrangements under long-lasting impregnated mosquito nets: differences during low and high malaria transmission seasons. - Fernando, S.D.; Abeyasinghe, R.R.; Galappaththy, G.N.; Gunawardena, N.; Ranasinghe, A,C; Rajapaksa, L.C. (My University, 2009)
Sleeping arrangements under long-lasting impregnated nets (LLIN) were recorded in 2467 households during the low malaria transmission season (May-June 2007) and the same families were followed up during the high malaria transmission season (December 2007-January 2008) in two malaria-endemic areas of Sri Lanka. Approximately 800 households each from the three main ethnic groups were studied. The number of families lost to follow-up was 68. A significant increase was seen in the proportion of households using LLINs the previous night during the high transmission season (96%) compared with the low transmission season (90%) (P< or =0.001 for all three ethnic groups). When sleeping arrangements of the entire population were considered, priority to sleep under the LLIN was given to children under 5 years during both seasons. The percentage of children under five who slept under a LLIN increased from 75% during the low transmission season to 90% during the high transmission season. Utilisation of LLINs by pregnant women was low; only approximately 45% of pregnant women reported sleeping under a LLIN during both seasons. The study suggests the possible need for re-focusing of health education messages regarding the importance of LLIN use among pregnant women